Instilling Critical Pedagogy in the Italian Language Classroom Journal of Language Teaching and Research - Formato, G. (Journal of Language Teaching and Research, 2018)
This article explores theoretical underpinnings for the use of critical pedagogy in the Italian language learning classroom. Its description of various components of critical theory lends a historical context for critical pedagogy, particularly in the arguments of Gramsci and the Frankfurt School, that contrast with positivist tenets. These critical elements extend to the classroom in a Freirian framework, including concepts such as banking, coding, and conscientization. Such lenses apply to the realm of foreign language teaching, particularly aspects of transformative learning. Issues surrounding materials design are also considered. Avenues and opportunities for critical thinking are explored through lesson plan ideas, as well as possible thematic unit topic suggestions in Italian courses. This paper concludes with questions for future research by language scholars in the field of education, in addition to a call to action for educators of Italian.